Pengaruh Takaran Pupuk Kandang dan Kompos terhadap Pertumbuhan Daun Kangkung (Ipomea Reptans) Akuaponik - Rahmi Sri Sayekti; Djoko Prajitno; Didik Indradewa (Agrotechnology Innovation (Agrinova), 2018)
AbstractThe population increase will be accompanied by an increase in the food needed. The agricultural sector is an area which is wrought by the majority of the population in all over Indonesia. The need for land lots to do enough to be able to increase food needs people of Indonesia. Currently, function transfer land acquisition is one of the problems that make a decreased production of agricultural products. Aquaponics is an alternative to cultivate plants and fish in one place. This technique to integrate the cultivation of fish ( recirculation ) aquaculture in coupled with plants. The bucket filled with approximately 60 l then mixed with manure 250 g / 1000 l, manure 500 g / 1000 l, compost 250 g / 1000 l, compost 500 g / 1000 l, and water control without additional fertilizer. The application of organic fertilizers in the form of manure and compost Aquaponics water spinacs leaves to improved growth than without the application of organic fertilizer. The application of manure with measure 500 g / 1000 l results is the best growth aquaponics water spinach leaves. AbstrakJumlah penduduk yang meningkat akan diiringi dengan peningkatan kebutuhan akan pangan. Sektor pertanian merupakan bidang mayoritas yang dikerjakan oleh penduduk di Indonesia. Kebutuhan akan lahan yang luas harus dilakukan agar mampu mencukupi peningkatan kebutuhan pangan penduduk di Indonesia. Saat ini alih fungsi lahan merupakan salah satu masalah yang membuat produksi hasil pertanian mengalami penurunan. Akuaponik   merupakan   sebuah   alternatif   yang membudidayakan  tanaman  dan  ikan  dalam  satu  tempat.  Teknik  ini mengintegrasikan budidaya ikan (resirculating aquaculture) yang dipadukan dengan tanaman. Ember diisi air kurang lebih 60 L lalu dicampur dengan pupuk kandang 250 g/ 1000 l, pupuk kandang 500 g/ 1000 l, pupuk kompos 250 g/ 1000 l, pupuk kompos 500 g/ 1000 l, dan air kontrol tanpa penambahan pupuk. Aplikasi pupuk organik dalam bentuk pupuk kandang dan kompos mampu meningkatkan pertumbuhan daun kangkung akuaponik dibandingkan dengan tanpa aplikasi pupuk organik. Aplikasi pupuk kandang dengan takaran 500 g/1000 l memberikan hasil pertumbuhan daun kangkung akuaponik yang terbaik.